1996
DOI: 10.1209/epl/i1996-00387-4
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency dielectric spectroscopy on glycerol

Abstract: Dielectric spectroscopy has been performed on supercooled glycerol for frequencies 3 µHz ≤ ν ≤ 40 GHz and temperatures between 100 K ≤ T ≤ 500 K. Hence, the absorptive part of the dielectric susceptibility was measured at comparable frequencies as the dynamic susceptibility obtained by neutron and light scattering techniques. The characteristic timescales obtained from all experimental techniques essentially agree. However, the dielectric data as measured on the high-frequency wing of the loss spectra are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 17 publications
11
89
1
Order By: Relevance
“…This alignment seems to be considerably reduced, with the net effect that the relaxation spectra of iso-amyl bromide in 2-methaylpentane becomes like that of an amorphous polymer with a broad distribution of relaxation times 27 and a variety of other molecular liquids. 5,8,9 As mentioned earlier here, a variety of studies on supercooled liquid glycerol 21 have found that its relaxation spectra is more appropriately described by the H-N equation or by a nonexponential relaxation function, [17][18][19][20] and not by the Davidson-Cole relaxation function. 16 In view of the fact that the dielectric data on supercooled liquid glycerol had led originally to the discovery of a new relaxation function, it may be worthwhile to re-examine the new data in order to determine whether or not its relatively high dc conductivity and the consequent interfacial polarization ͑which can be substantial when the surface to volume ratio of the liquid is large͒ has not contributed significantly to the low-frequency wing of the spectra.…”
Section: A the Spectral Shape And The Effects Of The Solventmentioning
confidence: 73%
See 1 more Smart Citation
“…This alignment seems to be considerably reduced, with the net effect that the relaxation spectra of iso-amyl bromide in 2-methaylpentane becomes like that of an amorphous polymer with a broad distribution of relaxation times 27 and a variety of other molecular liquids. 5,8,9 As mentioned earlier here, a variety of studies on supercooled liquid glycerol 21 have found that its relaxation spectra is more appropriately described by the H-N equation or by a nonexponential relaxation function, [17][18][19][20] and not by the Davidson-Cole relaxation function. 16 In view of the fact that the dielectric data on supercooled liquid glycerol had led originally to the discovery of a new relaxation function, it may be worthwhile to re-examine the new data in order to determine whether or not its relatively high dc conductivity and the consequent interfacial polarization ͑which can be substantial when the surface to volume ratio of the liquid is large͒ has not contributed significantly to the low-frequency wing of the spectra.…”
Section: A the Spectral Shape And The Effects Of The Solventmentioning
confidence: 73%
“…The latter relationship is a combination of the Cole-Cole relaxation 14,15 and Davidson-Cole relaxation 16 functions. In recent studies, [17][18][19][20][21] of dielectric relaxation in supercooled liquids, the dielectric spectra of glycerol, which was originally found to have an asymmetric shape and had led to the formalism of the Davidson-Cole relaxation function, 16 have been described in terms of the stretched exponential, and H-N ͑Ref. 13͒ equations.…”
Section: Introductionmentioning
confidence: 99%
“…16) to calculate the static dielectric constant, for the force fields showing a better performance in the prediction of the dielectric spectrum in every case (water SPC, ethanol TraPPE.UA, ethylene glycol OPLS, propylene glycol GAFF, glycerol OPLS and MEA OPLS). Black circles represent experimental values obtained from different sources for the following systems: water [9.12], ethanol [16.18, 97], ethylene glycol [98], propylene glycol [99], glycerol [95,96,100,101] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Discussionmentioning
confidence: 99%
“…The plot follows the equation, ␥Ϸa(TϪT 0 ), with aϭ0.0179 and T 0 ϭ78.1 K. This in turn will lead to the VFT dependence of the dielectric relaxation time as suggested by Nagel and Dixon. 29 Lunkenheimer et al 30 have found a similar behavior of the stretched exponent with temperature for glycerol, though they did not show any fitting of the data. It may be remarked that T 0 agrees with that using the mode-coupling theory better than the VFT, however this need to be investigated in detail in future.…”
Section: ͑17͒mentioning
confidence: 93%